Effect of Kupa Fruit Extract Concentration (Syzygium polycephalum) on Decreasing Blood Sugar Levels of Alloxan-Induced Male Mice (Mus musculus) - Dharmayanti, Luky; Novia, Devi; Sella, Arinda Tri Pramay (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Kupa fruit is a rare fruit that has a blackish purple color which has antioxidant potential, in vitro research is supported by the high levels of antioxidants and vitamin C in kupa fruit so that it can reduce blood sugar levels. Syzygium polycephalum is a plant that contains flavonoids so it has pharmacological potential as an antidiabetic, because it contains flavonoid compounds which can be used as antidiabetic prevention. This research aims to find out how effective Kupa fruit extract is and determine the right dose to reduce minimum blood sugar levels in mice that have been induced by alloxan. The research used an alloxan-induced testing method. There were 30 mice grouped into 6 treatments including normal control group mice, negative group mice, positive control mice, kupa fruit extract at a dose of 500 mg/Kg BW, fruit extract at a dose of 750 mg/kg BW and fruit extract at a dose of 1000 mg/Kg BW. The inducer to increase blood sugar levels in mice was Aloxan monohydrate using a dose of 150 Mg/KgBW using the intraperitoneal route of administration. The extract was administered for 14 days, the blood sugar levels of H0, H7 and H14 were measured using a glucotest strip (Easy Touch GCU) by taking samples from mice whose blood was taken through the tail of the lateral vein. Analysis of Results Through the SPSS One Way Anova test, the test was continued with a confidence level of 95% (p<0.05) using Posct Hoc. The results of the research were that there was a change in effect, namely a decrease in blood sugar levels in mice treated with extract from kupa fruit and the most effective dose was a decrease in blood sugar levels in mice, namely a dose of 1000 Mg/KgBW, followed by a dose of kupa fruit extract of 750 Mg/KgBW and finally with a dose of 500 Mg/KgBB.